Reversal of systolic dysfunction in noncompaction and Wolff-Parkinson-White syndrome after accessory pathway ablation. Issue 6 (December 2021) - Rezkalla, Katrin; Gatterer, Edmund; Hasun, Matthias; Huber, Johannes; Stöllberger, Claudia; Weidinger, Franz
Abstract: In a previously healthy asymptomatic 18-year old male, Wolff-Parkinson-White syndrome (WPW) with left ventricular hypertrabeculation/noncompaction (LVHT) and systolic dysfunction was detected. Holter monitoring disclosed multiple long episodes of supraventricular tachycardia with a heart rate of about 110/min. After radiofrequency ablation of an epicardial posteroseptal accessory pathway with ante- and retrograde conduction, systolic function gradually normalized without any pharmacotherapy. After 32 months of follow-up, the patient remains asymptomatic with normal systolic function. WPW-induced tachycardiomyopathy may even occur in asymptomatic patients, who are so adapted to their arrhythmias that they do not recognize them. <Learning objective: Tachycardiomyopathy in Wolff-Parkinson-White syndrome may even occur in asymptomatic patients. They seem so adapted to their tachyarrhythmia that they do not recognize them. Radiofrequency ablation of the accessory pathway may lead to complete normalization of systolic function. If left ventricular hypertrabeculation/noncompaction in the presented patient is causal or a coincidence remains unknown. Genetic testing revealed no variants. Because of left ventricular hypertrabeculation/noncompaction cardiologic follow-up is indicated.>